Simulasi Aliran Dingin Pada Mesin Pembakaran Internal - Kholil Nur Ibrahim; Ari Irawan; Ferdyansah Ananta; Syahrul Pratomo; Trisma Jaya Saputra (Pusat Riset dan Inovasi Nasional, 2023)
The dynamics of fluid flow in the engine combustion cylinder is very important for preparing the air-fuel mixture. Internal Combustion Engine models are built with the help of CATIAV5R20 software. The model is then imported into the HYPER MESH Finite Element preprocessing tool for splicing analysis. The model is then loaded into the finite Element breaker application. Using ANSYS FLUENT, the results are further processed. At various minimum valve lifts, cylinder flow dynamics is examined using FEA. For various crank angles, from 0° to 720°, plots of dynamic velocity and motion magnitudes are displayed. Finally, various crank angles and valve lift speeds are compared.